PROGRAMMING FIELD AND TECHNOLOGY IS TODAY’S TOPIC (British Journal of Global Ecology and Sustainable Development, 2024)
The Philippine education system is strongly geared toward technological advancement in this era of the Industrial Revolution (IR 4.0). This study aims to evaluate the computer programming competence of selected grade 9 students of Philippine Science High School (PSHS), Cagayan Valley Campus, and identify their learning experiences and challenges for learning strategy. This study used a qualitative method using exploratory study. A semi-structured interview was used to determine the programming learning experience and challenges of the students. Purposive sampling was used with 29 grade 9 students. The main finding of this study is that PSHS students are competent when it comes to their level of computer programming competency. Based on their learning experiences, computer programming subject helps to improve their critical thinking skills, which serve as a tool to solve real-world problems and allows them to learn different programming languages. In addition, they learned the value of patience and improved creativity. Moreover, there were identified challenges when it comes to more technical aspects of programming, such as improper coding syntax, incorrect solutions to problems, and difficulty in debugging. Overall, students' computer programming competence is good but needs further enrichment to hurdle some technical challenges. The results of the study provide useful information for computer science teachers to improve teaching strategies and approaches further. This study provides additional knowledge to the existing literature on computer programming in the K to 12 curricula of the Philippines education system.